Gedung Sate as an Architectural Study Lays the Foundation for Sustainable Heritage Tourism - Dananjaya, Ahmad Ghazy (EMARA: Indonesian Journal of Architecture, 2026)
Gedung Sate, located in Bandung, West Java, is an architectural icon that reflects a blend of colonial and local Indonesian cultures. As one of the historic buildings, Gedung Sate holds significant cultural value and has become a major tourist attraction that represents the historical and cultural identity of the nation. This study aims to explore the cultural and architectural significance of Gedung Sate as an important heritage site within the context of tourism and cultural preservation. The research method used is a descriptive qualitative approach, analyzing the design elements of Gedung Sate and its connection to the history and socio-cultural influences during its construction. The findings show that Gedung Sate functions not only as a government building but also as a cultural symbol that represents Indonesia's ethnic, religious, and historical diversity. The novelty of this research lies in a deeper understanding of Gedung Sate's role in cultural heritage tourism, as well as its contribution to preserving and promoting local values to the wider public. This study also opens opportunities for further research on the preservation of historic buildings within the context of modern tourism.